Ubezpieczenie społeczne twórców i artystów — wybrane zagadnienia - Świątek-Rudoman, Justyna (Wydawnictwo Uniwersytetu Wrocławskiego, 2019)
Creative and artistic activity in the context of being the subject of social insurance raises a lot of controversy. It is a result of the fact of its specificity related to the irregularity of the work and income combined with the contribution charges at the level of entrepreneurs. The author analyzes and assesses the current legal regulations related to social insurance of professional authors and artists, in particular the role of the decision of a commission determining when such activity is commenced and its impact on the arising of the insurance obligation and the right to benefits. In addition, the author presents and discusses the proposed changes in the scope of including this group in a separate social insurance system that assumes the establishment of suitable support mechanisms which will allow for the real participation of these people in the system.
Keywords: social insurance; professional authors and artists; separate insurance system